First Report of Ascotis selenaria imparata Walk. (Lepidopter: Geometridae) as a Pest of Moringa pterigosperma Gertn. - Kulkarni, N.; Kalia, Shamila; Sambath, S.; Joshi, K. C. (Indian Forester, 1996)
No abstract